Understanding How Resilience is Measured in the Organizational Sciences. Issue 2 (26th May 2020) - Cheng, Shannon; King, Danielle D.; Oswald, Frederick
ABSTRACT: Resilience is a topic of growing interest in the workplace; however, regarding its definition and measurement, a wide range of perspectives and idiosyncrasies persist. We take a closer look at the state of resilience through item-level analyses of 14 publicly available measures. In Study 1, relevance ratings revealed that many items from the measures were not aligned with subject matter experts' (SMEs) conceptualizations of resilience. In Study 2, SMEs were able to sort the relevant items reliably into eight categories. In Study 3, four factors summarized participant responses to these items, and these factors aligned with the categories from Study 2. Moreover, resilience scales based on these four factors demonstrated expected patterns of convergent and discriminant validity. Implications for resilience theory and measurement are discussed.